Pentingnya Sertifikat Halal Meningkatkan Sektor Ekonomi Pelaku Usaha Usaha Mikro Kecil dan Menengah (UMKM) - Syafrida; Arihta Ester Tarigan; Warsito; Suwardi (Universitas Muhammadiyah Kotabumi, 2026)
Abstrak This study examines the importance of halal certification for micro, small, and medium enterprises (MSMEs/UMKM) in Indonesia as mandated by Article 4 of the Halal Product Assurance Law (UUJPH), which requires all products circulating in the country to be halal-certified. Despite government efforts through regulations, online registration, and free certification programs such as SEHATI, many UMKM products remain uncertified or use non-legal halal labels, leaving consumers without legal protection and certainty. Using normative legal research with a qualitative approach based on secondary data, this study finds that halal certification is crucial for UMKM products as it increases sales, expands market access, strengthens competitiveness in national and international markets, supports community economic growth, and ensures legal protection for Muslim consumers’ rights.